STRATEGIES FOR THE DEVELOPMENT OF EDUCATIONAL INSTITUTIONS IN PUBLIC ADMINISTRATION: MANAGERIAL, ORGANIZATIONAL AND INNOVATIVE ASPECTS - Tambovska, Kristina (European Science, 2025)
The monograph is dedicated to the study of educational management within the context of public administration. The work analyzes the theoretical and methodological foundations of educational institution management, particularly in the context of decentral